Nitric oxide levels are not changed in saliva of patients infected with hepatitis C virus - Tavares,Fernando N. (2005)
The aim of this investigation was to determine nitric oxide metabolite levels in saliva samples from hepatitis C virus-positive patients in an attempt to test the hypothesis if increased levels of nitric oxide metabolites correlates with the presence of HCV-RNA in saliva. Saliva of 39 HCV-positive patients and 13 HCV-negative patients, without clinical or laboratorial evidence of liver disease were tested for nitric oxide metabolites. HCV-RNA was detected in serum and saliva by a RT-PCR method and nitric oxide level was determined by evaluation of its stable degradation products, nitrate and nitrite. No differences were found between the concentration of nitrite in saliva from HCV patients and controls, in despite of the presence or not of HCV RNA in saliva. Patients with HCV and cirrhosis had higher concentrations of nitrite but not significantly different from the control group or the groups of anti-HCV patients without cirrhosis. Increased levels of nitrite were not detected in anti-HCV positive patients, an indirect indication that chronic sialoadenitis are infrequent in these patients or occurs with low intensity not sufficient to increase nitric oxide metabolite levels in saliva.